Truth Concealed: The Crux Interpretum for Deception in Tobit and Judith - Spoelstra, Joshua Joel (Journal of early Christian history, 2025)
In the books of Judith and Tobit, a main character repeatedly employs deception as they interact with other players in the respective compositions. This deception is expressed in half-lies, part-truths, and intentional misdirection or double meaning. Since the prohibition against false testimony is one of the laws of the Decalogue, it is problematic that Judith, the paragon of piety and virtue, and Raphael, one of the seven archangels of God disguised as an Israelite, interact in this manner. This religio-ethical tension is the focus of this article which argues that each Jewish novella contains an imbedded hermeneutical key which contextually deciphers said deceptive conduct; moreover, each crux interpretum is provided by the character who functions in the mendacious guise. Through a literary analysis of Jewish novellas in general and the relevant passages specifically and through a cultural analysis of exilic and diasporic contexts, Jewish identity negotiation during the Second Temple period is constructed. In the end, a well-rounded understanding of the religio-ethical tensions in Tobit and Judith are extrapolated, yet not completely assuaged; indeed, for tensions in hagiography to mirror one’s own (communal) existence is probably intentional and to be appreciated.